2015
DOI: 10.1590/2359-3997000000098
|View full text |Cite
|
Sign up to set email alerts
|

The role of melatonin in diabetes: therapeutic implications

Abstract: Melatonin referred as the hormone of darkness is mainly secreted by pineal gland, its levels being elevated during night and low during the day. The effects of melatonin on insulin secretion are mediated through the melatonin receptors (MT1 and MT2). It decreases insulin secretion by inhibiting cAMP and cGMP pathways but activates the phospholipaseC/IP3 pathway, which mobilizes Ca 2+ from organelles and, consequently increases insulin secretion. Both in vivo and in vitro, insulin secretion by the pancreatic is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 87 publications
(106 reference statements)
3
62
0
5
Order By: Relevance
“…In addition to this dichotomy, we find that melatonin can have conflicting impacts on target tissues, such as the pancreatic beta cell, in both rodents and humans [49,111,140], and highly variable effects on systemic glucose homeostasis and insulin sensitivity [28,29,111,141,142]. In vitro, melatonin inhibits insulin secretion by lowering cAMP and cGMP production [27,49,[143][144][145]. This effect is logical in humans, presuming that melatonin acts to suppress insulin during the night, effectively sensitising the beta cell in preparation for breakfast, but is more difficult to rectify in night-time eating rodents.…”
Section: The Pancreatic Response To Melatoninmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition to this dichotomy, we find that melatonin can have conflicting impacts on target tissues, such as the pancreatic beta cell, in both rodents and humans [49,111,140], and highly variable effects on systemic glucose homeostasis and insulin sensitivity [28,29,111,141,142]. In vitro, melatonin inhibits insulin secretion by lowering cAMP and cGMP production [27,49,[143][144][145]. This effect is logical in humans, presuming that melatonin acts to suppress insulin during the night, effectively sensitising the beta cell in preparation for breakfast, but is more difficult to rectify in night-time eating rodents.…”
Section: The Pancreatic Response To Melatoninmentioning
confidence: 96%
“…The pros and cons of melatonin therapy for glycaemic control in humans With regard to treatment of type 2 diabetes with melatonin, the number of controlled clinical trials is somewhat limited, and the results are often mixed, with both positive and negative effects on glycaemic control being reported [27,145,151,152]. Evidence from animal and human studies indicates that melatonin or synthetic melatonin receptor agonists can alter glucose homeostasis [5,145,153].…”
Section: Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Molecular and immunocytochemical studies confirmed the presence of melatonin receptors MT1 and MT2 in the islets of Langerhans and also in human pancreatic tissue [13]. MT1 and/ or MT2-mediated melatonin action decreases glucose-stimulated insulin secretion in isolated rat pancreatic islets and rat insulinoma beta-cells.…”
Section: Melatonin Effects On Adipocytesmentioning
confidence: 54%
“…Показано, что у беременных с ГСД снижены связывающая способность рецептора ГЛЮТ4 и транспорт глюкозы в жировую ткань и скелетные мышцы [71,75,76]. Применение мелатонина и стабилизация циркадного рит-ма нормализуют метаболизм, оптимизиру-ют течение беременности и развитие плода [28,49,77]. Таким образом, результаты эксперимен-тальных и клинических исследований, рас-ширившие наше представление о механизмах регуляции углеводного обмена и энергети-ческого метаболизма, указывают на возмож-ность прогнозирования осложнения будущей беременности сахарным диабетом еще на этапе планирования семьи и своевременного прове-дения профилактических мероприятий, вклю-чающих прежде всего нормализацию суточного ритма сна и бодрствования, энергетического метаболизма, антиоксидантного статуса и при необходимости терапию с использованием ме-латонина.…”
unclassified